Therapeutic Strategies in HCC: Radiation Modalities. (3rd August 2016) - Gallicchio, R.; Nardelli, A.; Mainenti, P.; Nappi, A.; Capacchione, D.; Simeon, V.; Sirignano, C.; Abbruzzi, F.; Barbato, F.; Landriscina, M.; Storto, G.
Abstract : Patients with hepatocellular carcinoma (HCC) comply with an advanced disease and are not eligible for radical therapy. In this distressed scenario new treatment options hold great promise; among them transarterial chemoembolization (TACE) and transarterial metabolic radiotherapy (TAMR) have shown efficacy in terms of both tumor shrinking and survival. External radiation therapy (RTx) by using novel three-dimensional conformal radiotherapy has also been used for HCC patients with encouraging results while its role had been limited in the past for the low tolerance of surrounding healthy liver. The rationale of TAMR derives from the idea of delivering exceptional radiation dose locally to the tumor, with cell killing intent, while preserving normal liver from undue exposition and minimizing systemic irradiation. Since the therapeutic efficacy of TACE is being continuously disputed, the TAMR with 131 I Lipiodol or 90 Y microspheres has gained consideration providing adequate therapeutic responses regardless of few toxicities. The implementation of novel radioisotopes and technological innovations in the field of RTx constitutes an intriguing field of research with important translational aspects. Moreover, the combination of different therapeutic approaches including chemotherapy offers captivating perspectives. We present the role of the radiation-based therapies in hepatocellular carcinoma patients who are not entitled for radical treatment.